Análises in silico de genes associados à embriogênese somática em cana-de-açúcar - Cavalcante, Victor Ramos (2020)
Indirect somatic embryogenesis (ISE) is one of the most used regeneration pathways to obtain sugarcane genetically modified plants. ISE regulatory genes have been widely studied in monocotyledonous and dicotyledonous plants, and act as activators of the expression of gene cascades or promoting cell growth and differentiation. In contrast, in sugarcane, there are few reports in the literature with these genes involved in ISE. Thus, the present study aimed to i) search for putative homologous genes responsible for the regulation of ISE (families: BABYBOOM, WUSCHEL, LEAFY COTYLEDON, VIVIPAROUS1, and AGAMOUS-LIKE) in sugarcane (SP80-3280 and Saccharum spontaneum); ii) analyze the phylogeny between the sugarcane amino acid sequences and their homologous in Arabidopsis thaliana and Poaceae species; iii) design ideal primers for studying the expression of sugarcane ISE-related genes. BLAST and BLASTp searches were carried out in the Phytozome, NCBI, UniProt, and Gramene databases to obtain homologous sequences of the five gene families in corn, sorghum, rice, and A. thaliana. Thus, phylogenetic analyzes of amino acid sequences were performed with the aid of the software CLUSTALW and MEGAX, which showed evolutionary proximity between the proteins of Zea mays, Sorghum bicolor, S. spontaneum, and SP80-3280 in all the studied genes. In silico analyzes indicated that they may have more than one gene from the BABYBOOM, WUSCHEL, and VIVIPAROUS1 families regulating the pathways of ISE in sugarcane. In addition, with the aid of the PRIMER3 software, 8 pairs of primers with ideal parameters were obtained to be used in future analyzes of gene expression to understand more deeply the mechanisms of ISE.